2021
DOI: 10.3390/nano11081952
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation on Impacts of Fibronectin, Heparin–Chitosan, and Albumin Coating of Bacterial Nanocellulose Small-Diameter Vascular Grafts on Endothelialization In Vitro

Abstract: In this study, we contrast the impacts of surface coating bacterial nanocellulose small-diameter vascular grafts (BNC-SDVGs) with human albumin, fibronectin, or heparin–chitosan upon endothelialization with human saphenous vein endothelial cells (VEC) or endothelial progenitor cells (EPC) in vitro. In one scenario, coated grafts were cut into 2D circular patches for static colonization of a defined inner surface area; in another scenario, they were mounted on a customized bioreactor and subsequently perfused f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 107 publications
1
31
0
Order By: Relevance
“…Increasing cell adhesion and proliferation in static and dynamic culture conditions of human saphenous vein endothelial and endothelial progenitor cells [37] Carbodiimide cross-linker…”
Section: Fn Covalent Bindingmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing cell adhesion and proliferation in static and dynamic culture conditions of human saphenous vein endothelial and endothelial progenitor cells [37] Carbodiimide cross-linker…”
Section: Fn Covalent Bindingmentioning
confidence: 99%
“…Other strategies for Fn covalent immobilization on hydrogel surfaces using an avidinbiotin-binding system have also been described in the literature [34], as have those involving surface activation with hydrazine hydrate [35] or via a polydopamine-coating process [36]. Recently, Wacker et al reported the biofunctionalization of bacterial nanocellulosehydrogel-based vascular grafts (BNCs) with human albumin, Fn, or heparin-chitosan [37]. Briefly, BCN surfaces were activated with 1-cyano-4-dimethylamino pyridinium tetrafluoroborate (CDAP).…”
Section: ] Fibrinogenmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main aims in vascular prosthesis research is therefore to develop an ideal vascular prosthesis claiming the possibility of sterilization, storage and rapid availability, no or at least low cytotoxicity, good handling in surgical processing, no induction of external body complaints, no foreign body reaction, low thrombogenicity, variability of caliber; wall thickness; and length, and stability with elasticity and porosity with sufficient tightness [ ]. Various surface coatings, for example, attempt to improve artificial vascular prosthesis material [ ], [ ], [ ], [ ]. Specifically, the direct and fastest possible cell colonization on the different coatings with endothelial cells was investigated in this context by many groups so far [ , , ], [ ], [ ].…”
Section: Introductionmentioning
confidence: 99%
“…Various surface coatings, for example, attempt to improve artificial vascular prosthesis material [ ], [ ], [ ], [ ]. Specifically, the direct and fastest possible cell colonization on the different coatings with endothelial cells was investigated in this context by many groups so far [ , , ], [ ], [ ]. In addition to the reduction of thrombogenicity, a fast endothelialization of the vascular prosthesis should reduce intimal hyperplasia and thus prevent stenoses.…”
Section: Introductionmentioning
confidence: 99%